Regulation of Pdx1 by oxidative stress and Nrf2 in pancreatic beta-cells - Baumel-Alterzon, Sharon; Scott, Donald K. (Frontiers in Endocrinology, 2022)
The beta-cell identity gene, pancreatic duodenal homeobox 1 (Pdx1), plays critical roles in many aspects of the life of beta-cells including differentiation, maturation, function, survival and proliferation. High levels of reactive oxygen species (ROS) are extremely toxic to cells and especially to beta-cells due to their relatively low expression of antioxidant enzymes. One of the major mechanisms for beta-cell dysfunction in type-2 diabetes results from oxidative stress-dependent inhibition of PDX1 levels and function. ROS inhibits Pdx1 by reducing Pdx1 mRNA and protein levels, inhibiting PDX1 nuclear localization, and suppressing PDX1 coactivator complexes. The nuclear factor erythroid 2-related factor (Nrf2) antioxidant pathway controls the redox balance and allows the maintenance of high Pdx1 levels. Therefore pharmacological activation of the Nrf2 pathway may alleviate diabetes by preserving Pdx1 levels.